The Factors of Safety Ethics Issues among Construction Industry Personnel - Moris, Nila; Sarpin, Norliana; Mohamed, Sulzakimin; Ta Wee, Seow; Khalid, Zailawati (Research in Management of Technology and Business, 2022)
The construction industry is one of Malaysia’s largest industries and it has grown in recent years in coordination with rapid of growth of our modern world. The construction industry faces low safety ethics quality and safety concerns with unsafe, accidents, and death because of the main cause of dishonest behavior and conduct causes which can lead to other problems in workplace safety and health. Therefore, the objectives of this study are to identify the top safety ethics issues, to investigate the factors that cause safety ethics issues, and to study the strategies in controlling the safety issues in Public Work Department in Kapit, Sarawak. This study involves 70 construction personnel who works at Public Work Department in Kapit, Sarawak as the respondents. The research methodology adopted in this research is quantitative methods and the instrument that use to collect the data is questionnaires survey. The data collected was then analyse by using the Statistical Package for the Social Science (SPSS) software. The result of this study shows that the top safety ethics issues is non-compliance of specification and detail design when handling a construction project. The factors that cause safety ethics issues is the leader completely ignore the contribution of some team members and favour others instead. Besides, the results show the strategies in controlling the safety ethics issues is all personnel must receive the necessary workplace health and safety training when starting a job, changing jobs or using new techniques or technology. In conclusion, the research is aims to provide awareness to governments as well as organizations about the importance of safety ethics in the workplace.